Interacciones medicamentosas en pacientes con trombosis venosa profunda en los servicios de medicina “C” y cirugía “A” del Hospital Regional docente de Trujillo durante febrero del 2004 - febrero del 2007 - Roca Santos, Marilyn Elizabeth (2007)
The present study is descriptive, retrospective type and cross-section, and it was developed with the purpose of determining the medicaments interactions in the treatment of Deep Vein Thrombosis (DVT) in the patients hospitalized in the services of Medicine "C" and Surgery "A" of the Hospital Regional Docente de Trujillo (H.R.D.T.). 55 Clinical Histories were reviewed of which the 69,1% (38 patients) carry out the inclusion requirements. Of these was analyzed 281 prescriptions/day of hospital stay, which were put under evaluation to determine the medicamentosas interactions that they appeared in prescriptions/day by means of the analytical bibliographical method. Of the 38 analyzed Clinical Histories, it found that the 61,57% of prescripciones/día (173) presented medicaments interactions; being the most frequent Warfarin - Heparin (20.46%), Warfarin - Dalteparin (5.76%), Warfarin - Tramadole (5.76%). It determined that the percentage of Medicaments Interactions of Clinical Significance 1, 2, 3 was 70,21% (33 interactions) of the 47 Identified Interactions; being these Warfarin - Heparin (27%), Warfarin - Tramadole (7.6%) and Warfarin - Enoxaparin (6.08%). It find also that the 68,09% (32 interactions) of the interactions have severity Moderate, 78,72 % (37interacciones) have Beginning of Action is Slow and that 53,19% (25 interactions) have documentation probable. The Medicaments Interactions of pharmacodinamics type were 48.13%, the of pharmacokinetics type were 18.74% and the unknown were 36,31% It also could observed that the 33.13% (29) of the patients were of feminine sex.